2020
DOI: 10.3389/fgene.2020.01009
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Analysis Reveals Hub Genes Involved in Chicken Intramuscular Fat and Abdominal Fat Deposition During Development

Abstract: Fat traits are important in the chicken industry where there is a desire for high intramuscular fat (IMF) and low abdominal fat. However, there is limited knowledge on the relationship between the dynamic status of gene expression and the body fat deposition in chicken. Transcriptome data were obtained from breast muscle and abdominal fat of female chickens from nine developmental stages (from embryonic day 12 to hatched day 180). In total, 8,545 genes in breast muscle and 6,824 genes in abdominal fat were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 45 publications
0
28
1
Order By: Relevance
“…A study comparing the transcriptomes of the intestine and muscle, between divergent feed-efficient broilers, showed that ACSBG2 influences the muscular lipid utilization and was among the highest expressed genes in muscle (Reyer et al, 2018). We, however, did not find high expression of ACSBG2 in breast muscle at the nine different developmental stages of the same 27 slow-growing chicken used in this study (Xing et al, 2020). This difference between the studies may be caused by using different chicken breeds that differ in their growth rate.…”
Section: Discussioncontrasting
confidence: 71%
“…A study comparing the transcriptomes of the intestine and muscle, between divergent feed-efficient broilers, showed that ACSBG2 influences the muscular lipid utilization and was among the highest expressed genes in muscle (Reyer et al, 2018). We, however, did not find high expression of ACSBG2 in breast muscle at the nine different developmental stages of the same 27 slow-growing chicken used in this study (Xing et al, 2020). This difference between the studies may be caused by using different chicken breeds that differ in their growth rate.…”
Section: Discussioncontrasting
confidence: 71%
“…RNA-seq is effective for identifying differentially expressed (DE) genes as well as quantifying transcriptomes ( 22 , 23 ). This technique has been frequently used in the functional analysis of lncRNAs/mRNAs in adipose tissue in cattle ( 24 27 ), sheep ( 28 ), pigs ( 29 ), and chickens ( 30 ). Jiang et al ( 25 ) isolated 3,716 candidate lncRNAs from fat samples from calves and adult cattle and confirmed their crucial role in cattle of various ages.…”
Section: Introductionmentioning
confidence: 99%
“…However, similar to GWAS for quantitative traits that are performed with SNPs, association analyses based on gene expression levels and phenotypic records can be carried out to detect candidate genes for traits of interest. In addition to association studies, weighted gene co-expression network analysis (WGCNA) is widely used in gene expression analyses to explore the correlation patterns among expression levels of genes and to associate gene co-expression network modules to traits [ 20 ], including breast muscle IMF [ 21 ].…”
Section: Introductionmentioning
confidence: 99%